Reframing Human Enhancement: A Population Health Perspective - Cabrera, Laura Yenisa (Frontiers in Sociology, 2017)
The dominant understandings on human enhancement, such as those based on the therapy–enhancement distinction or transhumanist views, have been focused on high technological interventions directly changing biological and physical features of individuals. The individual-based orientation and reductionist approach that dominant views of human enhancement take have undermined the exploration of more inclusive ways to think about human enhancement. In this perspective, I argue that we need to expand our understanding of human enhancement and open a more serious discussion on the type of enhancement interventions that can foster practical improvements for populations. In doing so, lessons from a population health perspective can be incorporated. Under such a perspective, human enhancement focus shifts from changing the biological reality of individuals, to addressing environmental factors that undermine the optimal performance of individuals or that can foster wellness. Such a human enhancement perspective would be consistent with a population health approach, as it pursues more equitable and accessible interventions, on the path to addressing social inequality. Human enhancement does not need to be only about high-technological interventions for a selected group of individuals; rather, it should be a continuous project aiming to include everyone and maximize the public benefit.